2022
DOI: 10.1002/ijgo.14130
|View full text |Cite
|
Sign up to set email alerts
|

Exploring barriers to antiretroviral therapy adherence among pregnant women: A scoping literature review

Abstract: Background Antiretroviral therapy (ART) is one of the most effective ways of preventing HIV‐related maternal mortality. However, the rates of retention in care and long‐term adherence remain extremely low. Objective The aim of this study was to explore barriers to antiretroviral therapy adherence among pregnant women. Search strategy The search for articles was conducted using EBSCO Host, PubMed, Google scholar, and Cumulative Index of Nursing and Allied Health Literature (CINAHL). Selection criteria The studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…HIV is one of the major public health problems, especially in developing countries, accounting for approximately 12% of maternal deaths during pregnancy and 2% during postpartum (Arias-Colmenero et al 2020 ; Kalungwe et al 2022 ). Africa is the most affected region worldwide, where most of the population including pregnant women is currently being treated with antiretroviral therapy (Arias-Colmenero et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV is one of the major public health problems, especially in developing countries, accounting for approximately 12% of maternal deaths during pregnancy and 2% during postpartum (Arias-Colmenero et al 2020 ; Kalungwe et al 2022 ). Africa is the most affected region worldwide, where most of the population including pregnant women is currently being treated with antiretroviral therapy (Arias-Colmenero et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Antiretroviral therapy was found to be the most effective way to reduce HIV-related maternal mortality and perinatal transmission of HIV (Moseholm et al 2022 ). HIV-positive pregnant women among other worries face poor adherence to ART, as a result, this affects the progress in the fight against maternal mortality (Kalungwe et al 2022 ). Despite these benefits, pregnant women must also cope with stressors that are affecting their health (Moseholm et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this progress and the proven efficacy of Option B+ (5), poor adherence to lifelong ART and low retention in care of pregnant and postpartum women living with HIV has remained an important programmatic challenge to the implementation of Option B+ especially in low resource settings (6)(7)(8)(9)(10)(11). A review of studies done between 2000-2020 identified barriers to taking ART among pregnant women that included financial constraints limiting access to food and transport, and side effects of the therapy (12). Additionally, high dropout rates from PMTCT care have been documented after delivery and at two years of follow-up among mothers living with HIV (13)(14)(15), suggesting that service integration and linking mothers to routine ART services were important determinants of retention in care.…”
Section: Introductionmentioning
confidence: 99%
“…A literature review showed that many factors influence the likelihood that pregnant women with HIV receive proper ARV treatment. Kalungwe et al [ 8 ] showed that, in Africa, factors related to side effects and financial constraints in accessing food, transportation, and medicines influenced adherence to ARV treatment. Other factors included culture, religion, lack of partner support, stigma, and discrimination.…”
Section: Introductionmentioning
confidence: 99%